Variable-temperature variable-load anti-carbon-deposition magnesium nitride-based carrier catalyst

By using a porous Mg3N2 support and gradient thermal synthesis technology, combined with variable temperature and load operation, and designing bimodal channels and active component density gradients, the problem of carbon deposition and deactivation of traditional catalysts under variable temperature and load conditions was solved, achieving high efficiency, stability and long life of the catalyst, which is suitable for green ammonia production.

CN121004019APending Publication Date: 2025-11-25BEIJING YINENG HYDROGEN SOURCE TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511150225.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-18
Publication Date
2025-11-25

AI Technical Summary

Technical Problem

Traditional catalysts are prone to carbon buildup and deactivation under variable temperature and load conditions, resulting in a shortened lifespan. Existing improvement schemes have failed to effectively solve the problem of adaptability to dynamic operating conditions, especially in the production of green ammonia.

Method used

By using porous Mg3N2 support, active components such as Ru, Fe, and Co, and additives such as K, Cs, Ba, and La, combined with gradient thermal synthesis and variable temperature and load operation, a bimodal pore structure and active component density gradient are designed to form a periodic temperature-resistant structure that inhibits carbon deposition.

Benefits of technology

It significantly improves the stability and activity of the catalyst under dynamic operating conditions, extends its lifespan by 3 times, reduces production costs and energy consumption, and enhances the efficiency and selectivity of ammonia synthesis reaction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121004019A_ABST
    Figure CN121004019A_ABST
Patent Text Reader

Abstract

The invention relates to a temperature-variable load-variable carbon deposition-resistant magnesium nitride-based carrier catalyst, and particularly relates to the technical field of catalysts. The catalyst is composed of a porous Mg3N2 carrier, an active component and an auxiliary agent. The specific surface area of the carrier is 30-150m < 2 > / g, and the pore diameter is in bimodal distribution: small pores of 5-20nm are enriched with active components, and large pores of 30-50nm are spatially isolated; the active component is at least one of Ru / Fe / Co and is dispersed in the form of particles with the particle size of 2-15nm; the auxiliary agent is at least one of K / Cs / Ba / La oxides; the distribution density gradient of the active components on the surface of the carrier is 1.5-3.0 times, and the axial concentration gradient is 0.05-0.2 wt% / mm. The preparation method comprises the following steps: roasting Mg (OH) 2 in NH3 / N2 at 600-800 DEG C to prepare the carrier; polyethylene glycol-6000 which is 1.5 times of the total molar weight of the active component and the auxiliary metal cations is used as a structure-directing agent, and pulse impregnation loading is carried out; gradient thermal synthesis is carried out (300 DEG C / 1h, 600 DEG C / 2h and 800 DEG C / 3h). During application, the reaction pressure is 5-30 MPa, the temperature reference is 400-500 DEG C and sine fluctuation is + / -20-50 DEG C (the period is 10-60 min), and the H2 / N2 molar ratio is switched over + / -0.5 every 30-120 min. The catalyst enables the carbon deposition amount to be 1t; the pressure difference rises 1t when the weight is 1.5 wt%; the pressure is 0.3 MPa, and the service life is gt; the time is 500 hours.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of catalysis technology, specifically relating to a temperature- and load-sustaining magnesium nitride-based catalyst with anti-carbon deposition properties. In particular, it relates to a supported catalyst for the synthesis of green ammonia (NH3) from green hydrogen and nitrogen, a catalyst based on a magnesium nitride (Mg3N2) support with temperature- and load-sustaining anti-carbon deposition properties, its thermal synthesis preparation method, and its application. Background Technology

[0002] Green ammonia specifically refers to ammonia synthesized by electrolyzing water using renewable energy, producing green hydrogen, and then synthesizing ammonia with nitrogen through a catalytic reaction. Compared to traditional fossil fuel-based ammonia production, green ammonia production can reduce carbon dioxide emissions by up to 90%. However, the intermittent nature of renewable energy power supply leads to fluctuations in green hydrogen supply, resulting in frequent start-ups and shutdowns of the ammonia synthesis reactor and drastic changes in operating conditions. These dynamic operating conditions pose a severe challenge to traditional ammonia synthesis catalysts—carbon deposition and deactivation are 3-5 times more severe than under constant temperature and load conditions, and catalyst life is shortened to less than 30% of the original design life.

[0003] Traditional catalyst deactivation mechanism through carbon deposition Mainstream industrial iron-based catalysts (such as molten iron catalysts) perform well under steady-state conditions, but reveal inherent defects under variable temperature and load conditions: 1. Thermodynamics: When the reaction temperature is below 450℃, the driving force of the Boudouard reaction (2CO→C+CO2) is enhanced, and trace CO impurities in the feed gas are converted into carbon deposits; when the temperature is above 500℃, the rate of methane cracking (CH4→C+2H2) increases exponentially.

[0004] 2. Kinetic level: When the partial pressure of hydrogen drops sharply (e.g., the H2 / N2 ratio changes from 3:1 to 1:5), the CH4 adsorbed at the active sites... x The fragments failed to hydrogenate and desorb in time, and then polymerized to form a graphitized carbon layer.

[0005] 3. Limitations of the carrier: The acidic sites on the surface of the alumina (Al2O3) carrier promote carbon chain growth. When the carbon deposition coverage reaches more than 60%, the active sites are completely physically isolated.

[0006] Experimental data show that, under simulated green electricity fluctuation scenarios (temperature fluctuation ±40℃ / hour, H2 / N2 ratio switching frequency 4 times / hour), after 200 hours of operation, the ammonia yield of commercial Fe / Al2O3 catalyst decreased to 45% of the initial value, the carbon deposition reached as high as 12.8wt%, and the reactor pressure difference increased by 2.3 times.

[0007] To address the problem of carbon buildup, academia has proposed three types of solutions, but all of them have limitations in application: Modification of active components: Adding precious metals such as ruthenium (Ru) to enhance hydrogenation capacity. Although Ru-based catalysts can reduce the tendency to carbon deposition, under dynamic operating conditions, Ru nanoparticles migrate and agglomerate due to temperature cycling, resulting in a specific surface area loss of more than 40%. More importantly, precious metals account for 70% of the total cost of the catalyst, making it difficult to meet the economic requirements for large-scale production of green ammonia.

[0008] Improved support: Alkaline supports (such as MgO and CaO) are used to neutralize acidic sites. Magnesium aluminum spinel (MgAl2O4) supports can control carbon deposition below 8 wt%, but their specific surface area drops sharply by 60% in high-temperature regions above 800℃, making them unable to withstand the temperature shocks of ammonia synthesis reactors. While molecular sieve supports possess shape-selective confinement effects, their microporous structure (<2 nm) is easily and completely blocked by carbon deposits.

[0009] Process control: Pre-sulfurization treatment or addition of steam to inhibit carbon deposition. Nickel sulfide (NiSx) modified catalysts initially reduce carbon deposition by 50%, but sulfur is gradually lost at high temperatures, and the protective effect disappears after 200 hours; although steam injection can vaporize carbon deposits, it leads to a 35% decrease in ammonia synthesis rate and exacerbates reactor corrosion.

[0010] The core contradiction of lack of adaptability to dynamic operating conditions In-depth analysis shows that the root cause of the failure of existing technical approaches lies in their inability to resolve the core contradiction of "dynamic operating condition adaptability": 1. Thermomechanical stress mismatch: The difference in the coefficient of thermal expansion between traditional catalyst supports (such as γ-Al2O3) and active components (such as Fe3O4) can reach 8 × 10⁻⁶. -6 / K, temperature cycling induces interfacial microcracks, providing preferential nucleation sites for carbon deposits.

[0011] 2. Mass transfer kinetics stagnation: When the H2 / N2 ratio changes rapidly, the gas diffusion rate in the carrier pores cannot match the change in surface reaction rate, and the local carbon-hydrogen ratio imbalance promotes carbon deposition.

[0012] 3. Lack of carbon storage space: Conventional carriers have a single pore size distribution (concentrated in 5-10nm), and carbon deposits quickly block the pores to form a diffusion barrier. The lack of macroporous structures (>50nm) makes it impossible for carbon deposition to be directionally channeled.

[0013] The support material needs to meet three characteristics simultaneously: high-temperature structural stability, surface alkalinity control capability, and multi-level pore design; at the same time, the catalyst needs to achieve spatial decoupling of active sites and carbon deposition sites at the microstructural level. Summary of the Invention

[0014] To overcome the shortcomings of the prior art, the present invention aims to provide a temperature- and load-resistant magnesium nitride-based support catalyst.

[0015] To achieve the above objectives, the present invention provides the following technical solution: A temperature- and load-resistant magnesium nitride-based catalyst with anti-carbon deposition, its preparation method, application, and ammonia synthesis system. I. Temperature- and Variable-Support Magnesium Nitride Supported Catalysts Resistant to Carbon Deposition This invention focuses on a high-performance temperature- and load-resistant magnesium nitride-based supported catalyst, which is ingeniously composed of the following components: (a) Carrier The carrier is porous Mg3N2. Its specific surface area is 30-150 m² / g. 2 The specific surface area, within the range of / g, provides ample space for the loading of subsequent active components and the conduction of chemical reactions. Furthermore, its pore size exhibits a carefully designed bimodal distribution: the first peak ranges from 5 to 20 nm, creating favorable conditions for efficient dispersion of active components and efficient reaction; the second peak ranges from 30 to 50 nm. This bimodal pore structure allows the catalyst to achieve a balance between mass transport and reactivity.

[0016] (ii) Active components The active component consists of at least one metal selected from Ru, Fe, and Co, comprising 1-10% of the total catalyst mass. These metals are uniformly and efficiently dispersed on the support in the form of particles with a diameter of 2-15 nm. Controlling the particle size ensures that the active component can fully exert its catalytic activity during the chemical reaction, laying a solid foundation for improving the overall performance of the catalyst.

[0017] (iii) Additives The promoter component consists of at least one of the oxides of K, Cs, Ba, and La, accounting for 0.5-8% of the total mass of the catalyst, which improves its stability and catalytic efficiency under complex reaction conditions.

[0018] (iv) Periodic temperature-resistant structure The periodic temperature-resistant structure of this invention is specifically characterized by a density gradient of 1.5-3.0 times for the active component on the support surface, achieved by adjusting the density ratio of the top to bottom regions of the support. This density gradient design enhances the catalyst's resistance to temperature changes, effectively ensuring its stability under different temperature conditions.

[0019] Furthermore, in the bimodal pore size distribution, macropores with pore sizes of 30-50 nm are spatially isolated from the active components, while the active components are mainly concentrated in the 5-20 nm pore size region. This spatial structure improves the utilization efficiency of the active components and avoids the potential decline in catalytic performance caused by interference between macropores and active components.

[0020] Furthermore, the gradient thermal synthesis process creates a periodic temperature-resistant structure. During this process, a concentration gradient of the active component forms along the axis of the support, with the gradient change rate controlled within 0.05-0.2 wt% / mm. This concentration gradient further enhances the catalyst's adaptability and stability under varying temperature conditions, providing a strong guarantee for its efficient operation in practical applications.

[0021] II. Preparation method of magnesium nitride-based supported catalyst with variable temperature and variable support for carbon deposition It includes the following key steps: (I) Preparation of magnesium nitride support with bimodal pore size First, the Mg(OH)₂ precursor was calcined in a Mg₃ / N₂ mixed gas environment. The temperature was gradually increased to 600-800℃ at a uniform heating rate of 5℃ / min, and calcined at this temperature for 4 hours. This yielded a magnesium nitride support with a bimodal pore size structure. In this process, the NH₃ / N₂ mixed gas not only provided the atmospheric environment for the reaction but also positively influenced the crystal structure and pore size distribution of the magnesium nitride support, resulting in a bimodal pore size distribution in the final support, thus creating conditions for the subsequent loading of active components.

[0022] (ii) Loaded active components and auxiliaries Next, the active component precursor, auxiliary agent precursor, and structure-directing agent were fully dissolved in water. The structure-directing agent used here was polyethylene glycol-6000, and its addition amount was calculated to be 1.5 times the total molar amount of the active component metal and the auxiliary agent metal cation. Subsequently, the above mixed solution was loaded onto the prepared support using an equal-volume impregnation method. This impregnation method ensures that the active component and auxiliary agent are uniformly distributed on the support surface, thereby fully leveraging their synergistic effect. It is worth mentioning that, to further optimize the loading effect, a pulse impregnation method was used in step (b), with three equal-volume loadings of the impregnation solution, each 10 minutes apart. This pulse impregnation method allows the active component and auxiliary agent to penetrate deeply and uniformly into the support, improving the robustness and uniformity of the loading, thereby enhancing the overall performance of the catalyst.

[0023] (III) Gradient thermal synthesis Finally, a gradient thermal synthesis step is performed, in which the supported catalyst is treated in stages under the protection of a N2 atmosphere: 1. Increase the temperature to 300℃ at a heating rate of 2℃ / min and hold for 1 hour. This low-temperature treatment helps the active components and additives to initially form a stable binding state on the carrier surface, while preparing for the subsequent heating process.

[0024] 2. Next, the temperature was increased to 600℃ at a heating rate of 5℃ / min and held for 2 hours. Within this temperature range, the interaction between the active component and the promoter and the support was further enhanced, and the structure of the catalyst gradually became stable.

[0025] 3. Finally, the temperature is increased to 800℃ at a heating rate of 3℃ / min and held for 3 hours. During the high-temperature stage, the active components form a concentration gradient along the axis of the support, thereby constructing a periodic temperature-resistant structure, which gives the catalyst excellent temperature adaptability and stability.

[0026] III. Application of temperature- and load-resistant magnesium nitride-based supported catalysts in ammonia synthesis reaction The temperature- and load-resistant magnesium nitride-based supported catalyst of this invention exhibits advantages in the ammonia synthesis reaction, and the specific reaction conditions are as follows: (a) Reaction pressure and temperature reference The reaction pressure is set in the range of 5-30 MPa, and the temperature reference value is controlled at 400-500℃.

[0027] (ii) Variable temperature operation The variable-temperature operation employs a periodic temperature fluctuation in the form of a sine wave. The amplitude is set between ±20-50℃, and the period is controlled between 10-60 min. During the temperature fluctuation, the heating rate is 5-15℃ / min, and the cooling rate is 3-10℃ / min. This periodic temperature fluctuation design simulates the temperature changes that may be encountered in actual industrial production, helping to improve the catalyst's adaptability and activity under complex operating conditions. Through sinusoidal temperature changes, the active sites of the catalyst can be activated at different temperature points, promoting the reaction while avoiding catalyst deactivation or reduced reaction efficiency caused by excessively high or low temperatures.

[0028] (III) Load Change Operation In terms of variable load operation, the H2 / N2 molar ratio is switched between 1.0 and 3.0 every 30-120 minutes, with a switching range of ≥±0.5. Furthermore, the gas flow rate change rate during H2 / N2 switching is ≤10% / s. This variable load operation mode allows for real-time adjustment of the reactant ratio according to the reaction progress, improving the selectivity and efficiency of the reaction. Simultaneously, controlling the gas flow rate change rate ensures the stability of the reaction process, avoiding shocks to the reaction system caused by excessively rapid changes in gas flow rate.

[0029] Furthermore, the temperature fluctuations are synchronized with the molar ratio switching, with temperature troughs corresponding to H2 / N2 = 1.0-1.8 and temperature peaks corresponding to H2 / N2 = 2.0-3.0. This synchronized and coordinated operation further improves the efficiency and selectivity of the ammonia synthesis reaction, enabling the catalyst to efficiently catalyze the ammonia synthesis reaction under complex conditions of varying temperature and load, effectively suppressing carbon deposition, and improving the catalyst's lifespan and stability.

[0030] IV. An ammonia synthesis system This invention also relates to an ammonia synthesis system, the core of which includes a temperature- and load-resistant magnesium nitride-based support and a control unit. The control unit is precisely configured to perform the aforementioned temperature- and load-resistant operations. Through precise control, the ammonia synthesis reaction can be ensured to proceed stably and efficiently under the set temperature- and load-resistant conditions. This control unit integrates temperature and gas flow control technologies, enabling real-time monitoring of various parameters during the reaction process and adjustments based on the preset temperature- and load-resistant modes. In terms of temperature control, it can achieve sinusoidal temperature fluctuations, controlling the heating and cooling rates; in terms of gas flow control, it can adjust the switching of the H2 / N2 molar ratio and ensure that the gas flow rate change rate is within a specified range. This intelligent control unit, combined with the high-performance temperature- and load-resistant magnesium nitride-based support, constructs an efficient and stable ammonia synthesis system, providing technical support for the development of the ammonia synthesis industry.

[0031] Beneficial effects of the present invention 1. Dual-peak pore structure enables directional carbon deposition. Based on the dual-peak pore size distribution (5-20nm and 30-50nm dual peaks) and spatial isolation design between macropores and active components of the carrier of this invention, the catalyst produces the following effects under dynamic operating conditions: the densely distributed active components in the 5-20nm channels ensure a high reaction rate, while the 30-50nm macropores serve as a preferential carbon deposition zone; after carbon deposition, it is confined inside the macropores, avoiding covering the active sites in the small channels, and the exposure rate of active sites remains >90% after 500 hours of operation; the reactor pressure difference rise is reduced to 1 / 4 of that of traditional catalysts (measured <0.3MPa), ensuring long-term operational stability.

[0032] 2. Gradient distribution structure resists temperature cycling stress. The active component distribution density gradient (top / bottom density ratio 1.5-3.0 times) of this invention, combined with the axial concentration gradient (0.05-0.2wt% / mm), produces a synergistic effect: the reactor axial temperature gradient (inlet > outlet) matches the active component concentration gradient, avoiding local hot spots and deactivation; under temperature fluctuations (±20-50℃), the gradient structure buffers thermal expansion stress, and the active component migration rate decreases by 60%; the catalyst's thermal shock cycle resistance is increased to more than 300 cycles (traditional supports <50 cycles), extending its lifespan by 3 times.

[0033] 3. Gradient thermal synthesis process enhances metal support anchoring. The gradient thermal synthesis procedure (segmented treatment of 300℃→600℃→800℃) directly results in: removal of surface hydroxyl groups in the low-temperature segment (300℃), formation of metal-nitride interfacial bonds in the medium-temperature segment (600℃), and completion of lattice embedding in the high-temperature segment (800℃); the interfacial bonding energy between the active component and the support is increased to 450kJ / mol (traditional impregnation method <300kJ / mol), resisting the erosion of variable temperature airflow; the agglomeration rate of 2-15nm particles under dynamic conditions is <5% (traditional catalysts >30%).

[0034] 4. Variable temperature and load operation suppresses the thermodynamic equilibrium of carbon deposition. Variable temperature and load operating parameters (temperature sinusoidal fluctuation ±20-50℃ / H2 / N2 ratio switching amplitude ≥ ±0.5) produce kinetic regulation effects: during temperature troughs (lower temperature range), the methane cracking reaction is suppressed, and the carbon deposition rate decreases by 70%; high-frequency switching of the H2 / N2 ratio (switching every 30-120 min) breaks the CH4... x Fragment aggregation balance is achieved, and the time for hydrocarbon imbalance is shortened to within 5 seconds; synchronous control of temperature and gas ratio enables real-time vaporization of carbon deposit precursors, and the amount of carbon deposits is controlled to <1.5wt%.

[0035] 5. Structure-directing agents accurately regulate the dispersion of active components. The addition of polyethylene glycol-6000 (1.5 times the total molar amount of metal cations) improves the microstructure: the structure-directing agent complexes with metal ions to form a uniform impregnation layer, increasing the dispersion of active components from 45% to 85%; the standard deviation of the 2-15nm particle size distribution is reduced to 2.1nm (compared to >4.5nm in traditional impregnation methods), resulting in a more uniform surface energy distribution; combined with pulse impregnation, pore blockage is avoided, and the carrier pore utilization rate reaches over 95%.

[0036] 6. System integration reduces overall energy consumption of green ammonia. The ammonia synthesis system (including catalyst and variable temperature and load control unit) achieves a leap in energy efficiency: dynamic operating condition adaptability allows the catalyst to maintain ammonia yield fluctuation of <5% in the 20%-100% load range; no reactor shutdown is required during renewable energy fluctuations, increasing the annual effective operating time to 8000 hours; the compression energy consumption per ton of green ammonia is reduced by 35% (due to stable pressure difference), and the overall production cost is reduced by 28%. Attached Figure Description

[0037] Figure 1 This is a diagram showing the bimodal pore structure and distribution of active components in the catalyst.

[0038] Figure 2 This is a temperature program diagram for gradient thermal synthesis.

[0039] Figure 3 This is the control logic diagram for variable temperature and load.

[0040] Figure 4 This is a time-series diagram for temperature-gas ratio synchronization. Detailed Implementation

[0041] The technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0042] Example 1: Catalyst Preparation and Structure Verification This embodiment aims to elaborate in detail the preparation process of the temperature- and load-resistant magnesium nitride-based supported catalyst and to fully verify its structure in order to verify the unique performance and microstructural characteristics of the catalyst.

[0043] Preparation steps: 1. Support Synthesis: 100g of Mg(OH)₂ precursor was placed in a tube furnace. Then, an NH₃ / N₂ mixture was introduced, with the volume ratio of NH₃ to N₂ controlled at 1:2. During this process, the temperature inside the tube furnace was gradually increased to 700℃ at a stable and uniform heating rate of 5℃ / min, and calcined at this temperature for 4 hours to obtain the Mg₃N₂ support. In this process, the Mg₃ / N₂ mixture not only provided the atmospheric environment for the reaction but also affected the crystal structure and pore size distribution of the support.

[0044] 2. Structural Characterization: The specific surface area and pore size distribution of the prepared Mg3N2 support were determined using an advanced BET test method (according to GB / T19587-2017 Nitrogen Adsorption BET Method). The test results showed that the specific surface area of ​​the support reached 112 m² / s. 2 The nitrogen vacancy concentration of the support exhibits a typical bimodal pore size distribution, with the first peak having a pore size of 5.2 nm and the second peak having a pore size of 41.3 nm. Simultaneously, the nitrogen vacancy concentration of the support was determined using XPS (X-ray photoelectron spectroscopy), showing a nitrogen vacancy concentration of 1.8 vacancy / nm. 2 .

[0045] 3. Impregnation Load: Prepare the impregnation solution. Weigh 0.52g RuCl3·xH2O. Calculations show that it contains Ru... 3+ 0.05 mol; simultaneously weigh 0.17 g K₂CO₃, which contains K +0.02 mol. In addition, 2.1 g of polyethylene glycol-6000 was weighed, and its addition amount was prepared according to 1.5 times the total molar amount of the active metal component and the auxiliary metal cation (0.07 mol). The above substances were thoroughly dissolved in 10 ml of deionized water to form a homogeneous impregnation solution. Then, using a pulse impregnation method, the impregnation solution was loaded onto a 5 g support in three equal portions, with each loading interval controlled at 10 minutes. This pulse impregnation method ensures that the active component and auxiliary agent are more uniformly and deeply loaded onto the support surface, thereby improving the catalyst performance.

[0046] 4. Gradient Thermal Synthesis: Under a protected N2 atmosphere, the loaded sample undergoes gradient thermal synthesis treatment. The specific temperature program is as follows: The temperature was steadily increased to 300℃ at a heating rate of 2℃ / min and maintained at this temperature for 1 hour. The main purpose of this stage was to effectively remove the hydroxyl groups on the support surface, creating a purer surface environment for subsequent reactions.

[0047] Next, the temperature was further increased to 600℃ at a heating rate of 5℃ / min and held for 2 hours. Within this temperature range, a chemical reaction occurs between the active component Ru and the support, gradually forming stable Ru-N bonds, which further enhances the interaction between the active component and the support.

[0048] Finally, the temperature was increased to 800℃ at a heating rate of 3℃ / min and held for 3 hours. Under high temperature conditions, the active component Ru gradually intercalates into the crystal structure of the support, thereby forming a catalyst.

[0049] 5. Product characterization: Statistical analysis of the Ru nanoparticle size using high-resolution TEM (transmission electron microscopy) revealed a particle size of 4.8 ± 0.9 nm. The particle size range has a significant impact on the activity and selectivity of the catalyst.

[0050] The distribution of the active components on the support was analyzed in detail using SEM-EDS (scanning electron microscopy-energy dispersive spectroscopy) line scanning technology. The results showed that the Ru density in the top region was 3.1 wt%, and in the bottom region it was 1.9 wt%, resulting in a density gradient ratio of 1.63. This data visually demonstrates the density gradient characteristics of the active components on the support surface.

[0051] The concentration gradient of the active component along the axis of the carrier was accurately measured using EPMA (electron probe microanalysis) technology, and the results showed that the axial concentration gradient was 0.12 wt% / mm.

[0052] Example 2: Application Test of Ammonia Synthesis This embodiment focuses on examining the practical application performance of the catalyst prepared in Example 1 in the ammonia synthesis reaction. By setting a series of operating conditions, the stability, activity, and anti-carbon deposition ability of the catalyst under variable temperature and load environments are comprehensively evaluated.

[0053] Operating conditions: 1. Catalyst: The Ru-K / Mg3N2 catalyst carefully prepared in Example 1 was selected, with a loading of 5 ml to ensure sufficient active sites in the reaction.

[0054] 2. Reactor: A fixed-bed reactor is used to provide a stable reaction space. The reaction pressure is controlled at 15 MPa, and the temperature baseline is set at 450℃. These two parameters were determined based on in-depth research on the thermodynamics and kinetics of the ammonia synthesis reaction, providing suitable basic conditions for the reaction.

[0055] 3. Variable Temperature Operation: During the reaction, the temperature fluctuates periodically in a sinusoidal pattern, with an amplitude set at ±30℃ and a period of 20 minutes. The heating rate is precisely controlled at 10℃ / min, and the cooling rate is 6℃ / min. This variable temperature mode simulates the temperature changes that may be encountered in actual industrial production, effectively examining the catalyst's adaptability and stability under fluctuating temperature conditions.

[0056] 4. Variable load operation: Within 0-30 minutes, the molar ratio of H2 / N2 is set to 1.5:1, and the gas flow rate change rate is controlled at 8% / s. The H2 / N2 ratio and flow rate change during this stage are intended to simulate specific reaction conditions and examine the catalyst performance under these conditions.

[0057] Within 30-60 minutes, the H2 / N2 molar ratio was switched to 2.8:1, with the gas flow rate change rate controlled at 5% / s. This periodic switching of the H2 / N2 molar ratio simulated the dynamic changes in reactant proportions in actual production, further investigating the catalyst's adaptability and activity.

[0058] 5. Synchronous Control: The control system synchronizes temperature fluctuations with the H2 / N2 molar ratio switching. Specifically, when the temperature is at a trough (420℃), the H2 / N2 ratio is 1.5; when the temperature is at a peak (480℃), the H2 / N2 ratio is 2.8. This synchronous control method fully leverages the synergistic effect of the catalyst under different temperature and reactant ratio conditions, improving the efficiency and selectivity of the ammonia synthesis reaction.

[0059] result: Throughout the test, key indicators such as ammonia yield, carbon deposit amount, and pressure difference were monitored and recorded in real time. Specific data are shown in the table below: Table 1: Key Indicator Data Table for Example 2

[0060] Meanwhile, TEM observation revealed that carbon deposits were only present in macropores of 30-50 nm, while the active sites in micropores of 5-20 nm were not covered by carbon deposits. This result indicates that the catalyst structure and operating conditions designed in this invention can effectively suppress the formation of carbon deposits at active sites, thereby ensuring the stability and activity of the catalyst during long-term operation.

[0061] Comparative Example 1 (Disruption of the bimodal structure) This comparative example aims to highlight the key influence of bimodal pore structure on catalyst performance by comparing the commercially available γ-Al2O3 single-pore support with the bimodal pore support of Example 1.

[0062] 1. Support: Commercial γ-Al2O3 was selected as the support, which has a single-peak pore structure with a pore size of 8.5 nm, which is in stark contrast to the bi-peak pore support in Example 1.

[0063] 2. Active components: The active component loadings were kept the same as in Example 1, i.e., Ru 5wt% and K2O 2wt%, to ensure that under the same active component conditions, only the influence of the support structure on the catalyst performance was examined.

[0064] 3. Operating conditions: The operating conditions of Example 2 shall be fully followed, including reaction pressure, temperature reference, variable temperature and load operation, etc., to ensure the accuracy and reliability of the comparison.

[0065] 4. Results: Under the same test conditions, ammonia yield and carbon deposition were monitored, and the specific data are shown in the table below: Table 2: Key Indicator Data Table for Comparative Example 1

[0066] Meanwhile, it was observed that the pressure differential surged to 0.82 MPa due to extensive carbon buildup clogging the pores. Compared to Example 2, the ammonia yield of the catalyst in this comparative example was significantly reduced, while the amount of carbon buildup increased substantially, fully demonstrating the importance of the bimodal pore structure in improving catalyst performance and suppressing carbon buildup formation.

[0067] Comparative Example 2 (Destructive Gradient Thermosynthesis) This comparative example compares the gradient thermal synthesis process with that of Example 1 by changing the gradient thermal synthesis process and using direct calcination at 800°C, highlighting the key role of gradient thermal synthesis in the structure and performance of the catalyst.

[0068] 1. Preparation: The same Mg3N2 support as in Example 1 was used. After impregnation with active components and additives, instead of using a gradient thermal synthesis method, the mixture was directly calcined at 800°C for 4 hours.

[0069] 2. Characterization: TEM observation revealed severe agglomeration of Ru particles, with the average particle size increasing to 28 nm. Simultaneously, EPMA analysis showed no concentration gradient of the active component along the support axis. This indicates that without gradient thermal synthesis, the dispersibility of the active component deteriorates, preventing the formation of a catalyst with a specific structure.

[0070] 3. Operating conditions: The same operating conditions as in Example 2 were maintained to accurately evaluate the effect of gradient thermal synthesis on the performance of the catalyst in the ammonia synthesis reaction.

[0071] 4. Results: Under the same test conditions, the ammonia yield was monitored, and the specific data are shown in the table below: Table 3: Key Indicator Data Table for Comparative Example 2

[0072] Meanwhile, due to Ru particle migration caused by temperature fluctuations, the specific surface area of ​​the catalyst decreased by 52% after 200 hours. Compared with Example 2, the ammonia yield of the catalyst in this comparative example decreased significantly in a short period of time, indicating that gradient thermal synthesis plays a crucial role in maintaining the structural stability and activity of the catalyst.

[0073] Comparative Example 3 (Destructive Variable Temperature and Load Operation) This comparative example compares the operation conditions of constant temperature and constant H2 / N2 ratio with the variable temperature and variable load operation of Example 2, highlighting the significant impact of variable temperature and variable load operation on catalyst performance.

[0074] 1. Catalyst: The same catalyst as in Example 1 was selected to ensure that the effect of operating conditions on catalyst performance was examined under the same catalyst conditions.

[0075] 2. Operation: During the reaction, the temperature and load are not changed, but the operating conditions are kept constant at 450℃ and H2 / N2 = 2.5:1.

[0076] 3. Results: Under the same test conditions, ammonia yield and carbon deposition were monitored, and the specific data are shown in the table below: Table 4: Key Indicator Data Table for Comparative Example 3

[0077] Raman spectroscopy revealed that carbon deposits covered the active sites in the form of graphite whiskers. Compared to Example 2, the ammonia yield of the catalyst in this comparative example decreased significantly with increasing operating time, while the amount of carbon deposits increased, fully demonstrating the importance of variable temperature and loading operation in suppressing carbon deposit formation and improving catalyst stability and activity.

[0078] Test method notes: Specific surface area: GB / T19587-2017 Nitrogen adsorption BET method.

[0079] Pore ​​size distribution: ISO15901-2 mercury porosimetry.

[0080] Carbon deposits: Thermogravimetric analysis according to ASTM D6374.

[0081] Matters not covered in this invention are common knowledge.

[0082] See the distribution diagram of the bimodal pore structure and active components of the catalyst. Figure 1 The gradient thermal synthesis temperature program diagram is shown below. Figure 2 The variable temperature and load control logic diagram is shown below. Figure 3 The temperature-gas ratio synchronization time sequence diagram is shown below. Figure 4 .

[0083] The above embodiments are only for illustrating the technical concept and features of the present invention, and are intended to enable those skilled in the art to understand the content of the present invention and implement it accordingly. They should not be construed as limiting the scope of protection of the present invention. All equivalent changes or modifications made in accordance with the spirit and essence of the present invention should be covered within the scope of protection of the present invention.

Claims

1. A temperature- and load-resistant magnesium nitride-based supported catalyst, characterized in that, It consists of the following: Support: Porous Mg3N2, specific surface area 30-150 m² 2 / g, the pore size has a bimodal distribution: the first peak is 5-20nm, and the second peak is 30-50nm; Active component: at least one metal selected from Ru, Fe, and Co, accounting for 1-10% of the total mass of the catalyst, dispersed in the support as particles with a particle size of 2-15 nm; Additives: at least one of the oxides of K, Cs, Ba, and La, accounting for 0.5-8% of the total mass of the catalyst; Periodic temperature-resistant structure: The distribution density gradient of the active component on the carrier surface is 1.5-3.0 times, and the distribution density is the density of the top region of the carrier / the density of the bottom region.

2. The temperature- and load-resistant magnesium nitride-based supported catalyst according to claim 1, characterized in that: In the bimodal pore size distribution, the macropores with a pore size of 30-50 nm are spatially isolated from the active components, while the active components are concentrated in the pore size region of 5-20 nm.

3. The temperature- and load-resistant magnesium nitride-based supported catalyst according to claim 1, characterized in that: The periodic temperature-resistant structure is formed through gradient thermal synthesis, and the active component forms a concentration gradient along the axis of the carrier, with a gradient change rate of 0.05-0.2wt% / mm.

4. A method for preparing the temperature- and support-resistant magnesium nitride-based supported catalyst according to any one of claims 1-3, characterized in that, include: (a) The Mg(OH)2 precursor was calcined in an NH3 / N2 mixture at a temperature of 5℃ / min to 600-800℃ for 4h to obtain a bimodal pore size magnesium nitride support. (b) The active component precursor, the auxiliary agent precursor and the structure directing agent are dissolved in water, wherein the structure directing agent is polyethylene glycol-6000 and its addition amount is 1.5 times the total molar amount of the active component metal and the auxiliary agent metal cation, and is loaded onto the carrier by the equal volume impregnation method. (c) Gradient thermal synthesis: segmented processing under N2 atmosphere: ① Maintain at 300℃ for 1 hour, 2℃ / min → 300℃ ②5℃ / min→600℃ and hold for 2 hours, ③3℃ / min→800℃ for 3h.

5. The method for using a temperature- and load-resistant magnesium nitride-based supported catalyst according to claim 4, characterized in that: In step (b), the pulse immersion method is used, with the immersion liquid being applied in three equal amounts, with each application 10 minutes apart.

6. The application of the temperature- and support-resistant magnesium nitride-based supported catalyst according to any one of claims 1-3 in the ammonia synthesis reaction, characterized in that: Reaction pressure 5-30 MPa, temperature reference value 400-500℃; Variable temperature operation: The temperature fluctuates periodically in the form of a sine wave, with an amplitude of ±20-50℃ and a period of 10-60min; Variable load operation: The H2 / N2 molar ratio is switched between 1.0 and 3.0 every 30-120 minutes, with a switching range of ≥±0.

5.

7. The application according to claim 6, characterized in that: The temperature fluctuations and molar ratio switching are synchronized, with temperature troughs corresponding to H2 / N2=1.0-1.8 and temperature peaks corresponding to H2 / N2=2.0-3.

0.

8. The application of the temperature- and support-resistant magnesium nitride-based supported catalyst according to claim 6 in the ammonia synthesis reaction, characterized in that: In the temperature-changing operation, the heating rate is 5-15℃ / min, and the cooling rate is 3-10℃ / min.

9. The application of the temperature- and support-resistant, carbon-depositing magnesium nitride-based supported catalyst according to claim 6 in the ammonia synthesis reaction, characterized in that: During the variable load operation, the gas flow rate change rate during H2 / N2 switching is ≤10% / s.

10. An ammonia synthesis system, characterized in that: The invention comprises the temperature- and load-resistant magnesium nitride-based carrier and control unit as described in any one of claims 1-3, wherein the control unit is configured to perform the temperature- and load-resistant operation as described in any one of claims 6-9.